Blended learning engagement in higher education institutions: A differential item functioning analysis of students' backgrounds - Adams, Donnie (Universiti Utara Malaysia Press, 2020)
Purpose - Digital technology has transformed teaching and learning in such a way that it seems imperative lecturers and institutions need to adapt and adopt a blended learning model of instruction across disciplines. However, there is a scarcity of studies to determine the degree of students' engagement on blended or online university courses. The purpose of the study is to investigate students' cognitive engagement, emotional engagement, and behavioural engagement in a blended learning model of instruction as well as specifically assess their engagement based on demographic factors such as age, gender, field of study, ethnicity, and type of institution in leading Malaysian public and private higher education institutions.